(untitled) - Greydanus, Donald E. (New York, 2006)
This book sets forth the principles of clinical and psychosocial adolescent medicine clearly and concisely, at a price the market will bear. Includes numerous tables, charts, lists, and algorithms for easy access to the spectrum of clinical considerations.
Keywords: Adolescent medicine,Thuốc cho người trưởng thành